PROSPECTS FOR DEVELOPMENT OF HIGHER EDUCATION IN RUSSIA - Zhukova, Marina; Zhukov, Vadim; Markova, Tatiana; Tsabolova, Olga; Tretyak, Elena (Revista Inclusiones, 2020)
This article discusses the prospects for development of higher education in the Russian Federation. It has been revealed that the role and importance of intergovernmental agreements and contracts with higher schools are increasing. The Bologna Charter put forward competitiveness in education through a set of international ratings. It has been determined that the transfer of competition to the education sphere is ambiguously estimated by the subjects of educational activity. It has been proved that the challenges of globalization motivate differentiation of higher schools in terms of competitiveness criteria. It has been established that higher school in the era of significant challenges is designated to be a center for development of technologies and personnel, a real locomotive for industries and regions, should promote development of intellectual environment resistant against crisis trends in global world. It has been determined that in the ideal case, a modern university implies job training on the basis of standard or individual specification of trends and profiles, mutual scientific studies and developments, as well as their implementation on request.